In Silico Study And Synthesis Of Folic Acid-isoniazid Complex As A Potential Antituberculosis Agent - Tazizi, Mohammad Hafizie Dianel Mohd (2024)
This study aimed to design a novel conjugated compound, folic acid-isoniazid (FA-INH) conjugate, using ligand-based drug design and computational approaches, validated by molecular docking, and optimizing the key substrates for the conjugate synthesis through conventional and microwaved-assisted approaches. Out of 80 potential ligands, two compounds, C1 and C2, were chosen due to their high synthesis probability (p > 0.8). Both C1 and C2 underwent drug profiling and molecular docking assessments against GAPDH (PDB ID: 6IEP) at pH 7.4 and pH 6.0, as well as katG (PDB ID: 6ZJI) in both its wild type and mutant forms. The synthesis of C1 and C2 occurred in four phases, with Phase 1 and Phase 2 being further investigated and. Both C1 and C2 showed promise as drug candidates, with low ADMET (score = 9/22) and toxicity risks (score = 1.5/6.0). The binding interactions between C1 and C2 with GAPDH and KatG were favorable (ΔG C1 GAPDH pH 7.4 = -6.20 kcal/mol, ΔG C2 GAPDH pH 7.4 = -6.37 kcal/mol, ΔG C1 katG = -6.19 kcal/mol, ΔG C2 katG = -8.99 kcal/mol) with pH affecting binding strength towards GAPDH (ΔG C1 GAPDH pH 6.0 = -6.98 kcal/mol, ΔG C2 GAPDH pH 6.0 = -6.63 kcal/mol). Meanwhile on katG, C1 demonstrated better affinity for S315T (ΔG C1 S315T = -6.61 kcal/mol) and R418L (ΔG C1 katG = -7.02 kcal/mol). The microwaved-assisted approach gives highest yield of Phase 1 and 2 products (82.10 ± 0.291 % to 85.23 ± 0.495% for Phase 1 and 64.4 ± 0.183% to 67.3 ± 1.711% for Phase 2) compared to conventional approach (62.98 ± 0.383 to 67.44 ± 0.133 for Phase 1 and 59.86 ± 0.924% to 61.58 ± 0.160% for Phase 2).